2016
DOI: 10.1038/srep33685
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between neuronal activity and actin dynamics mimic the setting of an LTD synaptic tag

Abstract: Persistent forms of plasticity, such as long-term depression (LTD), are dependent on the interplay between activity-dependent synaptic tags and the capture of plasticity-related proteins. We propose that the synaptic tag represents a structural alteration that turns synapses permissive to change. We found that modulation of actin dynamics has different roles in the induction and maintenance of LTD. Inhibition of either actin depolymerisation or polymerization blocks LTD induction whereas only the inhibition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 40 publications
(77 reference statements)
7
22
0
Order By: Relevance
“…This suggests that a transient remodeling of actin is necessary for the capture of PRPs at activated synapses. [72][73][74] As shown previously, in our experimental setting, inhibiting the activation of CaMKII also blocks the setting of the synaptic tag, irrespectively of whether LTP or LTD was induced. 70,72,73 Interestingly, inhibiting actin polymerization rescued the effect of inhibiting CaMKII, showing that actin dynamics is downstream of CaMKII activation.…”
Section: Actin Camkii and The On-going Dynamics Of Synapsessupporting
confidence: 81%
See 3 more Smart Citations
“…This suggests that a transient remodeling of actin is necessary for the capture of PRPs at activated synapses. [72][73][74] As shown previously, in our experimental setting, inhibiting the activation of CaMKII also blocks the setting of the synaptic tag, irrespectively of whether LTP or LTD was induced. 70,72,73 Interestingly, inhibiting actin polymerization rescued the effect of inhibiting CaMKII, showing that actin dynamics is downstream of CaMKII activation.…”
Section: Actin Camkii and The On-going Dynamics Of Synapsessupporting
confidence: 81%
“…[72][73][74] As shown previously, in our experimental setting, inhibiting the activation of CaMKII also blocks the setting of the synaptic tag, irrespectively of whether LTP or LTD was induced. 70,72,73 Interestingly, inhibiting actin polymerization rescued the effect of inhibiting CaMKII, showing that actin dynamics is downstream of CaMKII activation. In LTD, we also showed that inhibiting actin polymerization is sufficient to create an artificial synaptic tag that can capture PRPs and express a maintained form of LTD by a tagging and capture mechanism.…”
Section: Actin Camkii and The On-going Dynamics Of Synapsessupporting
confidence: 81%
See 2 more Smart Citations
“…In this working model, synaptic cooperation and competition are determined by a balance between PRPs availability (source) and the strength of the tag (sink). In turn, the tag strength is a combination of the number of activated synapses and the ability that each synapse has in capturing PRPs (Fonseca, 2012;Szabó et al, 2016). Previous studies looking at competition in CA1 hippocampal synapses have shown that competition was correlated with the strength of the tag (Fonseca et al, 2004).…”
Section: Introductionmentioning
confidence: 99%